ACCOUNTING EDUCATION FOR CONTROLLERSHIP. - Vatter, W. J. (The Accounting Review, 1950)
Abstract In the real world of business affairs, however, the conception of the controller as a member of the management team, contributing to and concerned with the problems of overall administration and effective control, has grown. And it is becoming apparent that the subject of controllership (as apart from the professional aspects of public accounting) is not only relevant to, but important for collegiate business schools. Courses under the title of controllership are growing in number, and there are now at least thirty schools that offer a course in this subject. Part of this is attributable to the appearance of textbooks and other teaching materials emphasizing the viewpoint and the content of the controllership notion, but the underlying factor is the need for education of a different sort than is provided by professional specialization in accounting. On the whole, it is a fairly obvious fact that many of the students who "major" in accounting actually find their ultimate careers outside the field of public accounting.